Re-burying Artificially Exposed Surface of Viral Subunit Vaccines Through Oligomerization Enhances Vaccine Efficacy - Han, Xuelian; Cai, Zhuming; Dai, Yulong; Huang, He; Cao, Xiangwen; Wang, Yuan; Fang, Yingying; Liu, Gang; Zhang, Min; Zhang, Yuhang; Yang, Binhui; Xue, Wei; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Viral subunit vaccines often suffer low efficacy. We recently showed that when taken out of the context of whole virus particles, recombinant subunit vaccines contain artificially exposed surface regions that are non-neutralizing and reduce their efficacy, and thus these regions need to be re-buried in vaccine design. Here we used the envelope protein domain III (EDIII) of Japanese encephalitis virus (JEV), a subunit vaccine candidate, to further validate this important concept for subunit vaccine designs. We constructed monomeric EDIII, dimeric EDIII via a linear space, dimeric EDIII via an Fc tag, and trimeric EDIII via a foldon tag. Compared to monomeric EDIII or linearly linked dimeric EDIII, tightly packed EDIII oligomers via the Fc or foldon tag induce higher neutralizing antibody titers in mice and also protect mice more effectively from lethal JEV challenge. Structural analyses demonstrate that part of the artificially exposed surface areas on recombinant EDIII becomes re-buried in Fc or foldon-mediated oligomers. This study further establishes the artificially exposed surfaces as an intrinsic limitation of subunit vaccines, and suggests that re-burying these surfaces through tightly packed oligomerization is a convenient and effective approach to overcome this limitation.